Asset Bubbles: Predicate & Combat Against the Irrational Exuberance - Maitra, Debasish; Dey, Kushankur (Indian Journal of Finance, 2010)
An overwhelming tide of the financial tsunami has been inundating the whole world, resulting in substantial drop of asset prices and credit crunches. Bankruptcies, bailouts, defaults, foreclosures, etc. have become daily news headlines. Dozens of books, research papers, reviews and commentaries have rushed to be published to provide explanations on this once-in-a-century crisis. During the run-up in prices of internet stocks, financial commentators of the time argued on whether the higher prices were justified. Once the prices fell, answers seemed to be too obvious. Investors had got carried away, had not paid attention to the fundamental determinants of value of the assets that they were buying. They had succumbed to one of the most mortifying of all investor pitfalls: a speculative "bubble". The spectacular rise and fall of stock prices in the late 1990s and housing prices in the mid 2000s have been interpreted by many pundits as examples of asset bubbles. Economists typically use the term "bubble" to mean that the price of an asset differs from its "fundamental" intrinsic value, i.e. the present discounted value of dividends generated by the asset. For ages, many economists have been trying to define the ’bubble’ in different ways. Most of the economists fall into two schools. One school believes that the arbitrageurs push the overestimated market price to the sustained level. Other economists would say that asset prices become high when they are bought with hopes to sell further at higher prices.